Sistem Pendukung Keputusan Penyaluran Bantuan Pemerintah Menggunakan Algoritma Weigted Product - Reno Septia Erlangga; Yuza Reswan (Jurnal Media Infotama, 2022)
One factor that is strongly suspected to have contributed to reducing the number of poverty in Indonesia is the existence of a social assistance program by the central government. The social assistance program provided by the government on a regular basis to the community is very helpful if the distribution is right on target. The distribution of government assistance in Lunjuk Village, Seluma Barat District, Seluma Regency is still carried out conventionally, namely by providing assistance to all residents who are considered poor by the staff on duty without going through a selection process first. The amount of assistance provided by the government is limited so that not all residents can get this assistance. To facilitate the process of grouping residents, we need a system that can provide the right conclusions based on predetermined criteria. One of them uses a decision support system application. A system that can provide conclusions on the priority of beneficiaries based on the data that has been inputted. The conclusion generated by the application requires the right method to be implemented into the system and one of them is the weighted product method which can provide optimal solutions in the rating system. 1. The Decision Support System for the Distribution of Government Assistance Using the Weighted Product Algorithm in Lunjuk Village was built using the PHP programming language and MySQL database. The application can provide a priority list of beneficiaries based on the calculation results of the Weighted Product Algorithm using criteria weight data and data from Lunjuk Village residents.